25x² + 1 = 5
25x² + 1 - 5 = 0
25x² - 4 = 0 By difference of two squares
(5x)² - (2)² = 0
(5x - 2)(5x + 2) = 0
5x - 2 = 0 or 5x + 2 = 0
5x = 0 + 2 5x = 0 - 2
5x = 2 5x = -2
x = 2/5 x = -2/5
x = 0.4 x = -0.4
x = + 0.4 or -0.4
3/6 cause there are 3 evens and 3 odds on a dice
![\bf \begin{cases} f(x)=\cfrac{x}{x-9} \\ \quad \\ g(x)=\cfrac{-x}{x-3} \end{cases}\qquad f(x)+g(x)\implies \cfrac{x}{x-9}+\cfrac{-x}{x-3}](https://tex.z-dn.net/?f=%5Cbf%20%5Cbegin%7Bcases%7D%0Af%28x%29%3D%5Ccfrac%7Bx%7D%7Bx-9%7D%0A%5C%5C%20%5Cquad%20%5C%5C%0Ag%28x%29%3D%5Ccfrac%7B-x%7D%7Bx-3%7D%0A%5Cend%7Bcases%7D%5Cqquad%20f%28x%29%2Bg%28x%29%5Cimplies%20%5Ccfrac%7Bx%7D%7Bx-9%7D%2B%5Ccfrac%7B-x%7D%7Bx-3%7D)
get their LCD, like you'd with any other fractions, and add them up
The answer would be 1. The commutative postulate for multiplication. Hope this helped! Good luck! :)
So firstly, subtract x on both sides: ![-2y=-x+3](https://tex.z-dn.net/?f=%20-2y%3D-x%2B3%20)
Next, divide -2 on both sides, and your answer will be y = 1/2x - 3/2 , or the last option.